Population resettlement in Peru by mining and infrastructure projects: dialogue between practices and social theory - León, Camilo (2019)
Resettlement due to mining and infrastructure projects has become a relevant problem in Peru due to the growing number of projects juxtaposed with rural and urban habitats. Social Sciences have accumulated a body of studies that allow resettlements from multiple theoretical perspectives. Research shows residence, land use and mobility patterns of the population are not completely understood by companies and authorities in charge of resettlements, which therefore create more damage to those already affected. Companies and government use narratives about «development» and «risk» to legitimize the need of resettlement, but they are not necessarily capable of delivering the promises of a better future for those affected. Design of resettlement spaces follows a rationale of industrial and political control, far away from the traditional organization of the original towns. It is proposed that the government should norm resettlement procedures (limiting them as much as possible) including cultural, identity and participatory aspects in the design of new homes and towns.